The Responsibilities of Regional Water Supply Companies in Fulfilling Clean Water Needs are Associated with the Limited Liability Company Law - Dikha Anugrah; Suwari Akhmaddhian; Indah Maulani Putri (Universitas Kuningan, 2022)
The management of drinking water at the district or city level can take the form of a regional drinking water company (PDAM) and even in some districts or cities, now the regional drinking water company has changed its name to the regional public drinking water company (Perumda Air Drinking). Given the significant importance of the responsibility of the Regional Drinking Water Company (PDAM), the Regional Company must work professionally and efficiently in carrying out its business. The purpose of this research is to examine and examine how the regulation and implementation of the accountability of the Regional Public Water Company in meeting the demand for clean water in Kuningan Regency is related to regional regulations and Law no. 40 of 2007 concerning Limited Liability Companies. This research method uses an empirical juridical approach and collection techniques with primary, secondary and tertiary data, as well as data collection tools by means of observation and interviews, qualitative data analysis. The results of the study show that the Regional Water Supply Company in Kuningan Regency has implemented corporate social responsibility to the community in tackling the clean water crisis by providing assistance to fulfill clean water through tanker services as well as providing compensation in the form of cost reductions and providing a means for complaints to the public for services , making efforts to obtain new water sources and guarding and caring for a number of springs in Kuningan Regency carrying out a program of replanting tree species as a source of underground water storage.Â